Bibliometric: Social Media Marketing and Adoption in Indonesia - Kezia Arum Sary; Syarifah Hudayah; Zainal Abidin; Yohanes Kuleh (Syntax Corporation Indonesia, 2022)
This study conducts a bibliometric analysis of social media marketing and adoption in tourism development by reviewing previous studies in the world and Indonesia published in the Scopus database. The data obtained were analyzed using a quantitative approach to provide a representative picture in line with the practicality of bibliometric analysis in assessing the output, organization, authorship, and characteristics of topics. The focus was placed on the articles published between 2012 and 2021 and the findings showed an increasing interest in the studies related to social media marketing and social media adoption as well as an evolution of related academic research.